Characteristics and Levels of Mothers’ Knowledge about Management of Postpartum Blues Mental Disorder - I. Indarwati; M. Maryatun (P3M Universitas 'Aisyiyah Surakarta, 2021)
Background: Postpartum blues is a kind of mental disorder that often experienced by postpartum mothers and it is considered to be fine and believed to resolve itself after a few months. Because it does not bring a problematic case, it will be at risk of becoming depression which has more fatal consequences. The disorder can be resolved immediately if the family members understand the signs of symptom and the treatments that must be conducted. Goal: The study is aimed to know the characteristics and level knowledge of mothers about the treatment of postpartum blues disorder. Method: This study is conducted by cross sectional design and the subject is the mothers who have given birth yet or not yet or the family members. The technique of collecting data uses the android application that completed with questionnaire which designed specifically. The respondents are allowed to fill its online questionnaire with the gadget. Result: The result shows that most of respondents who are in 20 until 35 years old with the highly educated category, and most of them or 96.5% are as the housewife. Most of those mothers do not understand about the treatment of postpartum blues disorder. The mothers in highly educated category are mostly office employee. Recommendation: the KIE activity about the postpartum blues mental disorder should be held through the Integrated Healthcare Center (Posyandu) or Empowerment of Family Welfare (PKK) activities which collaborated with the Health Care Center in Jetis area. Thus, the further study must be conducted to investigate the difference on both of employee and housewife mothers about the treatment of postpartum blues.